Analisis Proses Morfologi Komposisi dalam Novel “Waktu dan Tenggara” Karya L. Dela Fimeta - Suprapti Suprapti (Lembaga Pengembangan Kinerja Dosen, 2026)
The novel Time and Southeast by L. Dela Fimeta, published on October 2, 2023, is one of the literary works in the romance genre that is interesting to study from a linguistic perspective, especially morphology. This study aims to analyze the morphological process of composition contained in the novel, focusing on the types, examples, and semantic aspects that arise in the use of word composition. The research method used is qualitative descriptive analysis with a literature review approach and text review. Data in the form of compositional words were collected from novel texts, then classified based on the type of composition, such as endocentric, exocentric, and idiomatic compositions. Semantic analysis is carried out to examine the meaning resulting from the composition process, both literal and connotative meanings that enrich the nuances of romance in the novel. The results of the study show that this novel uses word composition creatively to build aesthetic expression, strengthen characterization, and present a distinctive emotional nuance. The semantic aspects of word composition also contribute to the development of deep themes and language styles. In conclusion, the morphological study of composition in the novel Time and Southeast makes an important contribution to the development of morphological studies while enriching literary research that integrates language analysis in literary works.